Elementos constitutivos do trabalho docente em uma escola pública de educação básica: prescrições, atividades e ações - Santos, Maria Eliza Gama (2011)
The following research will be developed within the Graduate Program in Education of the Education Center of the Universidade Federal de Santa Maria (PPGE/CE/UFSM) as part of the investigative actions of the Research Project " Challenges for the Consolidation of Improvements in the Organization and Development of Educational and Training Processes of Teachers (DEPROCOM) ", linked to the Group of Studies, Research and Interventions (Gepi INOVAEDUC)" Educational Innovation, Educational Practices, and Teacher Training. " Our objective is to contribute with parameters to the organization of work contexts in order to enable teachers to take on a deliberate and conscious authorship and control their own work. We propose to answer the following research problem: "How do the conditions of work contexts influence the organization and development of teaching in Primary Education Public School? As a way to answer this research problem, we have been through the following issues: (1) How do you characterize the present framework of requirements in the context of teachers' work at the Primary Education School Studied?, (2) How does the activity of teacher integrates and articulates the different aspects of teaching conditions at the Primary Education School Studied? (3) How is the framework of the present actions in the context of teachers' work at the School of Basic Education Studied? It is a qualitative research, conducted as a case study, developed in a Municipal Elementary School, belonging to the City of Santa Maria, in the years 2010 and 2011, also defined as descriptive and analytical, with a view to nature of information collected. To understand the organization and operation of school work, it was used as sources of information: (1) participatory observations, made in meeting continuing education of teachers promoted by the school, (2) individual interviews with teachers to develop their professional activities in classroom and teachers who develop their work activities in the school management team and (3) guides for documentary analysis that guided the identification and collection of information in the documents used, the Political-Pedagogical Project of the Primary Education School studied and the Municipal Law No. 4696/93, 22/09/2003 establishing the Career Plan of the City Government. We found different contributions to studies of teaching in Primary education schools, in special; it is feasible to say that there is a prescriptive framework on the school work and the work of teachers contradictory in its constitution that confronts and legal opposition to the existing proposals and conditions. Working conditions is a major constituent element of the thinking of teachers about their work and have had direct impacts on the organization and their development. The teachers in performing their work activities mobilize elements of their own personal and professional characteristics, as well as characteristics of the school context, and from the articulation of these different elements, carry out their choices building standards for their performance in school. In general, teachers have done their job security in a lighter and simpler way. The complexity of most school activities has been neglected in terms of their forms of achievement, which have produced a representation of the actions that the school closer to the triviality of that complexity. There is a clear separation between the work of teachers and school, giving the impression that the school has not yet been fitted out to include the teacher's work, its organization and execution of work as an effective school.